'When We are in Crisis': Youth-Centered Transitional Justice, Police Violence, and Political Imaginaries. (14th March 2022) - Anderson, Patrick; Aushana, Christina; Collins, Caroline
ABSTRACT∞ : This article describes youth involvement in the voter-mandated transition to a fully independent, powerful community commission overseeing the San Diego (California) Police Department. We begin by describing the historical context of police violence against communities of color in San Diego, and previous attempts to practice transparency and accountability in public safety. We then situate our work with local high school students to engage directly in the transition process, and to imagine future models of public safety with youth justice at its core.